Processos licitatórios no Campus III da Universidade Federal da Paraíba: uma análise da performance dos pregões de ração e insumos de nutrição animal - Silva, Macicley Félix da (2021)
This research aimed to analyze the performance of bidding processes for the acquisition of feed and supplies for animal nutrition under the CCHSA/CAVN, Campus III of the Federal University of Paraíba, since through the tenders carried out, it was possible to notice the existence of difficulties in some of the processes which directly compromised the acquisition of these items for the institution. Faced with several changes and demands that the market started to demand, organizations have been increasingly concerned with presenting a favorable performance in their results, in order to provide a quality service with the proper application of public resources. Purchasing management has a fundamental role in this process by providing managers with subsidies capable of helping them to make the best possible decision, in relation to what they want to buy and contract. As a theoretical framework, this work was based on the theory of public management, focusing on public procurement, on new perspectives of governance when dealing with transparency, planning, sustainability and shared procurement. Public bidding and its modality, the electronic auction, were discussed, as well as the form of use via the price registration system and, finally, how the performance of public purchases works and the respective related variables. The research is classified in terms of its nature as applied, of the quantitative type, of an exploratory nature, and in terms of the means of investigation considered bibliographical, documental and field. As a time frame, the analysis was carried out from 2016 to 2020. Data collection was carried out with the physical and electronic processes as well as on the website of the federal government procurement portal and its treatment was carried out through the application of a checklist corresponding to the performance variables of public procurement. The results show that the performance presented has not been as expected due to internal and external problems to the organization, ranging from the planning phase of acquisitions, price surveys, process duration, server turnover to absence or shortage preparation of suppliers. Thus, there is a continuous need to improve the bidding processes so that it can satisfy everyone involved in obtaining the desired result.